Pemberdayaan Masyarakat Desa Bongo melalui Inovasi Pengelolaan Air Bersih dan Sanitasi Ramah Lingkungan untuk Pencapaian Tujuan SDGs - Lydia S. Tatura; Abdi Gunawan Djafar; Niniek Pratiwi (Universitas Negeri Gorontalo, 2024)
Coastal areas and small islands in the middle of the high seas are areas that are very poor in sources of clean water, so that problems arise in fulfilling the need for clean water. Water resources in the area are generally of poor quality, for example the groundwater is brackish or salty. The quality of the water is very poor because it contains very high levels of salt and organic matter. The area of Bongo Village, Batudaa Pantai District, Gorontalo Regency, Gorontalo Province is a coastal area that still needs a supply of clean water. The local community's water needs come from the mountains, and some depend on injection wells to provide clean water, however, the water from these injection wells still tastes salty or contains salt and the provision of these wells is not sufficient for all the houses in Bongo village. To achieve the goals of SDGs (clean water and sanitation) in the environmental sector by ensuring that the community achieves universal access to clean water and sanitation, then to improve environmental quality and health self-sufficiency, students solve existing problems by empowering Bongo Village Communities through Clean Water Management Innovations and Environmentally Friendly Sanitation for Achieving SDGs Goals.